Examination on Social Injustice in Contemporary Societies Amartya Sen's Approach - Orji, Chidi Paul; Nwagbara, Rufus Godswill; Chukwu, Peter Damian Ezechi; Egberongbe, Tijani Taiwo (NIU Journal of Legal Studies, 2025)
The article looks at Amartya Sen’s perspective on the injustice problem as well as the idea of justice. To understand Sen’s view of justice, one must consider his critique of Rawls’ Theory of Justice. One could read Sen’s Idea of Justice as both a critique of Rawls’ theory of justice and a suggestion for a different approach. Sen’s criticism of Rawls’ theory of justice led to the development of his own view of justice. Furthermore, by examining and understanding Sen’s notion of justice, Niti and Nyaya’s human reasoning is able to differentiate between injustice and justice. Adam Smith proposes the unbiased observer as the moral criterion in the Theory of Moral Sentiments. This concept is used by Sen to the question of political fairness. Sen offers the Capability Model as a remedy for the equal justice problem in his works. Keywords: Justice, Niti and Nyaya, Amartya Sen,